Perception of Staff Nurses on Quality Patient Care - Rane, Punam Prabhakar (Indian Journal of Nursing Sciences, 2024)
Introduction: Quality of care reflects how health-care services improve health outcomes. Nurses, as the largest health-care workforce, play a critical role. This study analyzed nurses’ perceptions of quality patient care and identified factors influencing it at MGM Hospital, Kamothe, India. Materials and Methods: A quantitative, descriptive survey was conducted with 106 nurses using convenient sampling. The study included nurses aged 20 or above working directly with patients and willing to participate administrative permission was obtained from the MS of MGM hospital. Data were collected through Google Forms from June 09, 2021 to June 19, 2021, with links distributed through WhatsApp to the nursing superintendent and ward incharge. Results: The majority (65%) of nurses held a neutral perception of quality patient care, followed by negative (25%) and positive (16%) perceptions. The highest mean perception score (61.9%) with the lowest standard deviation (SD 2) was observed for communication between nurses, patients, and relatives among factors promoting quality care. Conversely, equipment and consumables had the highest mean perception score (55.4%) with the highest SD (3) as factors hindering quality care. Conclusion: While communication is perceived positively by nurses, a significant portion holds neutral or negative views on quality patient care. Equipment and resources are areas needing improvement. Further research with a larger, representative sample and qualitative methods is recommended to inform targeted interventions for enhancing care quality at the hospital. This study encourages beginning researchers to explore similar topics with different variables on a larger scale.